Pattern of Dyslipidemia among Acute Coronary Syndrome (ACS) Patients at Nepalgunj Medical College: A Hospital Based Cross Sectional Study - Adhikari, Krishna Chandra; Bist, Aayush; Verma, Awadesh Kumar; Mahato, Bijay Kumar; Shah, Rojina (Journal of Nepalgunj Medical College, 2025)
Introduction: Dyslipidemia is a major risk factor for acute coronary syndrome, with varying patterns across ethnicities and regions, such as higher triglyceride levels in South Asians. Aims: To describe the demographic and dyslipidemia patterns among acute coronary syndrome patients. Methods: This hospital-based cross-sectional study, conducted from 25 April to 24 October 2024, using convenience sampling to enroll 95 patients diagnosed with acute coronary syndrome (unstable angina), Non-ST-segment elevation myocardial infarction, ST-segment elevation myocardial infarction admitted to the Intensive Care Unit of our center. Data were collected using a structured and semi structured proforma with demographic details, clinical findings, and laboratory results. Informed written consent was obtained from all participants. Results: Among the participants, 54 were male with majority from Nepalgunj (22.1%). Risk factor analysis revealed 64% of patients were smokers, 49% had hypertension, and 9% had type 2 diabetes mellitus. Only 5% of patients demonstrated dyslipidemia with isolated low High Density Lipoprotein Cholesterol. Non-ST segment elevation myocardial infarction was the most common presentation. Conclusion: Isolated low High Density Lipoprotein Cholesterol was the predominant dyslipidemia pattern in statin-naïve acute coronary syndrome patients in western Nepal, despite low overall prevalence suggesting regional variations, possibly due to exclusion of patients on lipid-lowering drugs. These findings highlight the need for targeted lipid screening in early management.